Effect of concentrated growth factors on function and Wnt3a expression of human periodontal ligament cells in vitro. (3rd April 2017) - Qiao, Jing; An, Na
Abstract: Concentrated growth factors (CGFs), the new generation of platelet concentrate products, appear to exhibit superior potential for tissue regeneration. However, there are only a few studies supporting this. This study was designed to investigate the effect of CGFs on proliferation and alkaline phosphatase (ALP) activity of human periodontal ligament cells (hPDLCs) in vitro . Furthermore, as bone homeostasis is fundamentally controlled by Wnt-mediated signals, we also investigated Wnt3a expression of hPDLCs after treatment of CGFs. hPDLCs and CGFs were obtained from the same volunteer. CGFs or combination of recombined human TGF-β1 (rhTGF-β1) and PDGF-AB (rhPDGF-AB) were added to hPDLCs in different concentrations. The rate of proliferation was analyzed by an MTT assay. ALP activity was assessed using p-NPP assay. Quantitative RT-PCR was used to evaluate the gene expression of Wnt3a. In a range of concentrations, CGFs significantly promoted the proliferation of hPDLCs in a dose-dependent manner. ALP activity was also enhanced by CGFs in a dose-dependent and time-dependent manner. The stimulatory effect of CGFs was much greater than rhTGF-β1 and rhPDGF-AB combination. Quantitative RT-PCR results showed that Wnt3a mRNA expression was increased at 24 h in hPDLCs treated by CGFs. CGFs can enhance hPDLCs proliferation and ALP activity and may have great potential in clinical and biotechnological applications.